ChemInform Abstract: Asymmetric Synthesis of cis‐Aminocyclopentenols, Building Blocks for Medicinal Chemistry. Issue 30 (29th July 2014) - Zaed, Ahmed M.; Grafton, Mark W.; Ahmad, Sajjad; Sutherland, Andrew
Abstract A rapid, relatively mild, and highly efficient one‐pot multistep process is developed for the preparation of (R)‐ and (S)‐aminocyclopenta‐2‐enes (III).